Financial misreporting and securities fraud — public and private enforcement - Mohd. Sulaiman, Aiman @ Nariman (LexisNexis, 2008)
Between 2004 and 2006 several companies in Malaysia were involved in financial misreporting probes by the securities regulators. In the majority of the cases of financial misreporting enforcement action was taken by these regulators. There does not appear to have been any private enforcement action taken in respect of financial misreporting in public companies. Where private actions have been taken over financial misreporting they have been applications for oppression remedies in private companies. Enforcement proceedings in public companies have not relied on oppression. This article discusses the various enforcement actions taken by the securities market regulators. It also discusses the possibility of private enforcement of securities law contraventions and whether the enforcement actions taken by the regulators could be useful in private enforcement. This article also considers whether the recent company and securities law amendments, ie, the Companies (Amendment) Act 2007 and the Capital Market and Services Act 2007 will assist shareholder activism in this area.